Immune dysregulation as a driver of bronchiolitis obliterans - Deng, Kuimiao; Lu, Gen (Frontiers in Immunology, 2024)
Bronchiolitis obliterans (BO) is a disease characterized by airway obstruction and fibrosis that can occur in all age groups. Bronchiolitis obliterans syndrome (BOS) is a clinical manifestation of BO in patients who have undergone lung transplantation or hematopoietic stem cell transplantation. Persistent inflammation and fibrosis of small airways make the disease irreversible, eventually leading to lung failure. The pathogenesis of BO is not entirely clear, but immune disorders are commonly involved, with various immune cells playing complex roles in different BO subtypes. Accordingly, the US Food and Drug Administration (FDA) has recently approved several new drugs that can alleviate chronic graft-versus-host disease (cGVHD) by regulating the function of immune cells, some of which have efficacy specifically with cGVHD-BOS. In this review, we will discuss the roles of different immune cells in BO/BOS, and introduce the latest drugs targeting various immune cells as the main target. This study emphasizes that immune dysfunction is an important driving factor in its pathophysiology. A better understanding of the role of the immune system in BO will enable the development of targeted immunotherapies to effectively delay or even reverse this condition.